Comprehensive Model of Bankruptcy and Forensic Accounting - Eka Wirajuang Daurrohmah; Ali Riza; Pesi Suryani; Dekar Urumsah (Jati: Jurnal Akuntansi Terapan Indonesia, 2022)
Going concern is an assumption of company establishment but some companies go bankrupt. Fraud can be a cause of bankruptcy, used to hide bankruptcy, and can occur due to bankruptcy. Potential fraud can occur in every main activity of a curator in resolving bankruptcy cases so the curator requires forensic accounting. The purpose of this study was to determine the importance of forensic accounting in bankruptcy cases resolved by a curator and exploring the model of the relationship between bankruptcy and forensic accounting. This study used a qualitative approach with semi-structured interviews. The respondents’ criteria were curators who had practiced for at least three years and had experiences in resolving bankruptcy assets. The data analysis was a content analysis, namely a relational analysis, with software Nvivo 11. The results of this study showed that, in carrying out their duties, there are obstacles that are commonly encountered by currators. Forensic accounting is important and helpful for curators’ work, especially related to fraud or verification of the accuracy of bankruptcy asset transactions and the process of valuing bankruptcy assets. However, not all curators understand forensic accounting